Perilaku Makan Sehat Perawat terhadap Kinerja Asuhan Keperawatan - Nurbaeti, Reidha Fitri; Gayatri, Dewi; Handiyani, Hanny (Journal of Telenursing (JOTING), 2023)
This study aims to review various studies related to healthy eating behavior and nursing care performance. The method used was a literature search on PubMed, Ebsco, ProQuest, and Clinical Key databases. The research results obtained five articles that met the inclusion criteria. The literature review found that nurses' healthy eating behavior can be influenced by various factors such as time of day, shift work, work environment, and work culture. In conclusion, fulfilling healthy nutrition is intended not only for patients but also for nurses. Healthy nurses will be able to provide quality nursing services. In conclusion, healthy eating impacts occupational health problems and the performance of nurses in hospitals, which are caused by wrong nutritional consumption habits that affect increasing body weight in nurses. Keywords: Performance, Healthy Eating, Nursing